Peningkatan Kemampuan Tact Anak dengan Autism Spectrum Disorder melalui Media Flash Card - Khairil Mursyidin; Bayu Pamungkas (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
This study aims to analyze improvements in tact skills in a child with Autism Spectrum Disorder (ASD) using flashcards. Communication barriers in children with ASD often manifest as difficulties in establishing a connection between environmental stimuli and appropriate verbal responses. The study subject was a 12-year-old sixth grader with ASD, identified by the initials FA. The research method used was Single Subject Research (SSR) with an A-B design. Data were collected through direct observation and analyzed using visual analysis techniques. The results showed a significant improvement in tact skills in subject FA. The baseline phase (A) showed a low and stable skill level with an average score of 22.0 and a flat trend. The intervention administered during phase (B) resulted in a surge in performance, with the average score increasing to 67.0 and showing a consistently upward trend. An analysis of the conditions revealed an immediate change of +40 points with a data overlap percentage of 0%. These findings demonstrate that flashcards are effective as a concrete visual aid.